Single-Nucleus Chromatin Accessibility and Epigenetic Study Uncover Cell States and Transcriptional Regulation of Epidermis in Hidradenitis Suppurativa - Safiya Haque; Suha Mohiuddin; Jasim Khan; Suhail Muzaffar; Sudeepthi Vejendla; Yanfeng Zhang; Masakazu Kamata; Lin Jin (Biomedicines)
Background/Objectives: Hidradenitis suppurativa (HS) is a complicated chronic inflammatory skin disorder characterized by recurrent and painful deep-seated nodules, abscesses, fistulae, scarring, and sinus tracts. HS most commonly affects high-density hair follicles and apocrine gland-rich regions of the body, including the axillae, inguinal folds, breasts, and perianal areas. Although genetic predisposition and environmental factors are known to contribute to the development and the severity of HS, the molecular mechanisms of HS are largely unknown. Methods: In this study, we employed global epigenetic and genomic data analysis and single-nucleus ATAC-seq (snATAC-seq) to profile the heterogeneity of HS-associated chromatin accessibility and define the underlying disease drivers. We additionally performed high-resolution immunofluorescence staining to confirm a novel candidate regulator. Results: We found that multiple skin development modules and molecular signal pathways were epigenetically dysregulated in HS basal CD49fhigh cells. Importantly, our snATAC-seq revealed a previously unraveled role for a transcription factor, ATF3, in transcriptionally regulating HS-associated genes. We also delineated the specific ATF3 expression pattern across the HS lesional skin. Conclusions: We characterize HS-specific epigenetic plasticity and chromatin state at the single-nucleus level and further underscore a possible mechanism for HS pathogenesis.